2015
DOI: 10.1002/dmrr.2626
|View full text |Cite
|
Sign up to set email alerts
|

Associations between clinical characteristics and chronic complications in latent autoimmune diabetes in adults and type 2 diabetes

Abstract: Patients with LADA had a lower prevalence of microvascular complications than patients with type 2 diabetes when the duration of diabetes was <5 years. Regression equation fitted by clinical characteristics can better predict the risk of microvascular complications in LADA than in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 42 publications
(68 reference statements)
2
20
1
Order By: Relevance
“…Consistent with this, in our study, up to 59.2% of E‐LADA patients have metabolic syndrome. This prevalence was seemingly higher than the rate of 41.9% reported in European LADA patients and the rate of 31.0% reported in another Chinese study . Analysis of the data in E‐LADA patients stratified by GADA titre showed that more components of metabolic syndrome were evident in E‐LADA patients with low titre of GADA.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Consistent with this, in our study, up to 59.2% of E‐LADA patients have metabolic syndrome. This prevalence was seemingly higher than the rate of 41.9% reported in European LADA patients and the rate of 31.0% reported in another Chinese study . Analysis of the data in E‐LADA patients stratified by GADA titre showed that more components of metabolic syndrome were evident in E‐LADA patients with low titre of GADA.…”
Section: Discussioncontrasting
confidence: 66%
“…Previous studies have confirmed that metabolic syndrome is prevalent in LADA patients; however, it is less prevalent compared with T2D patients. 14 24 Analysis of the data in E-LADA patients stratified by GADA titre showed that more components of metabolic syndrome were evident in E-LADA patients with low titre of GADA.…”
Section: Discussionmentioning
confidence: 99%
“…It also reported that more LADA patients required insulin therapy . Furthermore, our previous study showed a lower prevalence of microvascular complications in LADA in the early stage of diabetes . In this study, different levels of systolic blood pressure, BMI, FCP, TG and HDL‐C were also observed among patients with type 1 DM, LADA, type 2 DM and controls.…”
Section: Discussionsupporting
confidence: 66%
“…Participants were grouped into having LADA (n = 15, 12 men and 3 women) or type 1 diabetes (n = 15, 7 men and 8 women). Subgrouping of participants into LADA was based on the criteria suggested by the Immunology of Diabetes Society: age of onset after 30 years of age, the presence of at least one circulating autoantibody mentioned above, and insulin independence for the first 6 months after disease onset, as seen in other studies of LADA . A type 2 diabetes cohort (n = 23, 11 men, 12 women) and a cohort of age‐matched healthy control participants (n = 26, 11 men, 15 women) were also recruited.…”
Section: Methodsmentioning
confidence: 99%
“…12 Society: age of onset after 30 years of age, the presence of at least one circulating autoantibody mentioned above, and insulin independence for the first 6 months after disease onset, as seen in other studies of LADA. 13,14 A type 2 diabetes cohort (n = 23, 11 men, 12 women) and a cohort of age-matched healthy control participants (n = 26, 11 men, 15 women) were also recruited. Required cohort sizes were determined from changes in nerve excitability parameters observed in previous studies of participants with diabetes and were calculated at 80% power, with an α = .05.…”
mentioning
confidence: 99%